Social and informative saturation as a condition for the effective organization of independent activities of future translators and ways to implement it - Остапенко, Світлана Анатоліївна (Pedagogy of Higher and Secondary Education, 2013)
Ostapenko S. A. Social and informative saturation as a condition for the effective organization of independent activities of future translators and ways to implement it. The article deals with the notion of social-informational satiety, its influence on the students’ self-directed educational activity, evolution of modern and informational technologies application in educational process, describes forms and methods used in the process of future translators preparation